FACTORS RELATED TO PROVIDING TPT (TUBERCULOSIS PREVENTION THERAPY) IN THE UOBF WORK AREA OF PARENGAN HEALTH CENTER - Eka Ayu MBPS; Eko Winarti (Indonesian Health Literacy Journal, 2025)
Tuberculosis (TB) is a disease caused by Mycobacterium tuberculosis. TB can attack the lungs and can attack all parts of the body. TB is one of the top 10 causes of death and the main cause of one infectious agent. This study is an observational analytical study with a cross-sectional design. The results showed that the majority of respondents were female, highly educated (high school and above), were partners of TB patients, had a good level of knowledge, the distance from their residence to the Health Center was close, and they had received education from health workers. Variables related to the receipt of TB preventive therapy in TB household contacts were gender, education level, knowledge level, distance between residence and, and education about TPT from health workers. Variables that were not related were the age and kinship of respondents with TB patients. It can be concluded that out of 7 independent variables, there are 5 variables related to TPT.